Caring for the elderly and working with the aging population - Andrej Berdajs (University of Maribor Press, 2021)
Older people receive care and assistance in both formal and informal ways. About 4% of people aged over 65 are living in institutional care. Most of the help is provided by families and other informal carers. We must arrange assistance for informal carers and direct the care not only to the medical aspect but also to the social component. The social care component helps vulnerable older people to overcome the crisis caused by exclusion from their environment and reduction in their social network. This is an important opportunity for social pedagogical work, either in various institutions or through.